The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/wer.10708
|View full text |Cite
|
Sign up to set email alerts
|

Alternative methods for cleaning membranes in water and wastewater treatment

Abstract: Membrane fouling is caused by foulant deposition or adsorption through physical or chemical interactions on the membrane surface, causing the reduction of flux through the membrane. The main drawbacks of chemical agents used for cleaning are cost, damage caused on the membrane, and waste stream making the process unattractive. Alternative, methods such as ultrasound, enzymatic process, and osmotic backwashing were explored for membrane cleaning. Among all mentioned methods, micronanobubbles have been reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 115 publications
(145 reference statements)
0
2
0
Order By: Relevance
“…NaClO is the most used oxidant for membrane cleaning and removes both organic and biological foulants via oxidation and disinfection (Terán-Hilares et al, 2022), and enhances the detachment of organic molecules from the membrane by increasing their hydrophilicity. With ceramic membranes, Song et al (2016) showed that permeate flux can be restored using NaOH at 70 ± 1°C which hydrolyses colloids into fine particles, and organic matter into small molecules.…”
Section: Physicochemical and Chemical Cleaningmentioning
confidence: 99%
“…NaClO is the most used oxidant for membrane cleaning and removes both organic and biological foulants via oxidation and disinfection (Terán-Hilares et al, 2022), and enhances the detachment of organic molecules from the membrane by increasing their hydrophilicity. With ceramic membranes, Song et al (2016) showed that permeate flux can be restored using NaOH at 70 ± 1°C which hydrolyses colloids into fine particles, and organic matter into small molecules.…”
Section: Physicochemical and Chemical Cleaningmentioning
confidence: 99%
“…NaClO is the most used oxidant employed for membrane cleaning. It allows for the removal of organic and biological foulants via oxidation and disinfection processes [68,69]. It may degrade functional groups of natural organic matter (NOM) into ketonic, carbonyl, and aldehyde groups, leading to their hydrolysis at high pH levels [144].…”
Section: Physio-chemical and Chemical Cleaningmentioning
confidence: 99%
“…In brief, the methods of membrane cleaning are categorized into three groups: chemical, physical, and physio-chemical. It should be emphasized that physical cleaning is adopted to remove reversible fouling while chemical cleaning to remove irreversible fouling [26,68,69].…”
Section: Introductionmentioning
confidence: 99%
“…Membrane fouling can be avoided by regular cleaning with chemicals such as sodium hypochlorite or NaOH. However, the more frequently a membrane is cleaned with chemicals, the shorter its life-span [15,22,34].…”
Section: Introductionmentioning
confidence: 99%